ANALISIS KANDUNGAN FITOKIMIA DAN AKTIVITAS PENSTABIL OKSIGEN SINGLET DARI DAUN KELAPA - Katja, Dewa (Sam Ratulangi University, 2008)
The objectives of study was to determine phytochemicals content and singlet oxygen quencher (SOQ)activities examination in 2 type (DMA and GKN) of coconut leave. Analyses of phytochemicals based ontotal phenolic, flavonoid and condensed tannins. To detect the involment of singlet oxygen inphotodegradation 5 ppm erythrosine solution containing 2 types of extracts were exposed under 4000 luxfluorescent light for up to 5 hours. The result showed that coconut leave of DMA type possessed totalphenolic, flavonoid and tannin content were 149.27; 3725 and 1822 mg/kg, whereas for type of GKN was138.73; 4625 and 2110.81 mg/kg, respectively. The DMA leave exhibited the highest singlet oxygenquenching activities compared by GKN leaves. The results also indicated that concentration of both theextracts increased with increasing. The results also indicated that concentration of both the extractsincreased with increasing singlet oxygen quenching activities. These result suggested that phenoliccompounds groups having singlet oxygen quenching activitiesÂ Keywords: phenolics, coconut leave extract, singlet oxygen quenching